Dietary isoflavone intake is not statistically significantly associated with breast cancer risk in the Multiethnic Cohort - Morimoto, Yukiko (Br J Nutr, 2014)
Given high soy intake and low incidence rates in Asian countries, isoflavones, substances with an estrogen-like structure occurring principally in soybeans, are postulated to be cancer-protective. We examined the association of dietary isoflavone intake with breast cancer risk in 84,450 women (896 in situ and 3,873 invasive cases) who were part of the Multiethnic Cohort (Japanese Americans, whites, Latinos, African Americans, and Native Hawaiians) with wide ranges of soy intake. The absolute amount of dietary isoflavone consumption estimated from a baseline food frequency questionnaire was categorized into quartiles, with the top quartile further subdivided to examine high dietary intake. The respective intakes for the quartiles (Q1, Q2, Q3, lower and upper Q4s) were 0-<3.2, 3.2-<6.7, 6.7-<12.9, 12.9-<20.3, and 20.3-178.7 mg/day. After a mean follow-up of 13 years, hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated using Cox regression stratified by age and adjusted for known confounders. Linear trends were tested by modeling continuous variables of interest assigned the median value within the corresponding quartile. We observed no statistically significant association between dietary isoflavone intake and overall breast cancer risk (HR [and 95% CI] for upper Q4 vs. Q1: 0.96 [0.85-1.08]; P-trend=0.40). While the test for interaction was not significant (P=0.14), stratified analyses suggested possible ethnic/racial differences in risk estimates, with a suggestion that higher isoflavone intake may be protective in Latina, African American, and Japanese American women. These results agree with previous meta-analyses showing no protection at low intake levels but suggesting inverse associations in high-soy consuming populations.